Growth Performance and Pork Quality of Finishing Pigs Fed Diet Supplemented with Sacha Inchi Oil and Herbal Plants - Oanh, N. C.; Thu, C. T. T.; Don, N. V.; Hornick, J. L. (Tropical Animal Science Journal, 2023)
The study aimed to evaluate the effects of dietary soybean oil (SO) substitution with Sacha inchi oil (SIO) supplemented with herbal plants (HP, Bidens pilosa, Angelica sinensis, and Ramulus cinnamomi) on growth performance, carcass characteristics, and pork quality parameters. A total of 144 Duroc × (Landrace × Yorkshire) crossbred pigs (63.1 ± 0.4 kg) were randomly allocated to one of the three dietary treatments: a basal diet containing 2% SO without HP (CONT), a basal diet containing 1% SO, 1% SIO and 1% HP (TRT1), and a basal diet containing 2% SIO and 1% HP (TRT2). Each treatment includes 4 replicate pens containing 12 pigs, balanced by sex and body weight. The experiment lasted for 70 days. The results show no effects of the dietary treatments on average daily gain, average daily feed intake, and feed efficiency. Likewise, there were no differences in carcass moisture losses, lean percentage, pH, and colors between the dietary treatments. The pigs fed the SIO diets with HP had lower backfat thickness (p=0.02) than their counterparts fed the SO diet. In pork, a significant decrease in lipid and cholesterol, and an increase in polyunsaturated fatty acids (PUFA), especially omega-3 and omega-6, were found (p<0.01) in the SIO groups when compared to the control one. The PUFA percentage increased linearly with the levels of SIO. In conclusion, replacing SO with SIO associated with HP did not affect animal performance but produced a leaner carcass and upgraded pork quality.